Incidence and natural history of challenge‐proven cow's milk allergy in European children – EuroPrevall birth cohort. Issue 8 (18th May 2015) - Schoemaker, A. A.; Sprikkelman, A. B.; Grimshaw, K. E.; Roberts, G.; Grabenhenrich, L.; Rosenfeld, L.; Siegert, S.; Dubakiene, R.; Rudzeviciene, O.; Reche, M.; Fiandor, A.; Papadopoulos, N. G.; et al.
Abstract Background Cow's milk allergy (CMA) is one of the most commonly reported childhood food problems. Community‐based incidence and prevalence estimates vary widely, due to possible misinterpretations of presumed reactions to milk and differences in study design, particularly diagnostic criteria. Methods Children from the EuroPrevall birth cohort in 9 European countries with symptoms possibly related to CMA were invited for clinical evaluation including cows' milk‐specific IgE antibodies (IgE), skin prick test (SPT) reactivity and double‐blind, placebo‐controlled food challenge. Results Across Europe, 12 049 children were enrolled, and 9336 (77.5%) were followed up to 2 years of age. CMA was suspected in 358 children and confirmed in 55 resulting in an overall incidence of challenge‐proven CMA of 0.54% (95% CI 0.41–0.70). National incidences ranged from 1% (in the Netherlands and UK) to <0.3% (in Lithuania, Germany and Greece). Of all children with CMA, 23.6% had no cow's milk‐specific IgE in serum, especially those from UK, the Netherlands, Poland and Italy. Of children with CMA who were re‐evaluated one year after diagnosis, 69% (22/32) tolerated cow's milk, including all children with non‐IgE‐associated CMA and 57% of those children with IgE‐associated CMA. Conclusions This unique pan‐European birth cohort study using the gold standard diagnostic procedure for food allergies confirmed challenge‐proven CMA in <1% of children up to age 2. Affected infants without detectable specific antibodies to cow's milk were very likely to tolerate cow's milk one year after diagnosis, whereas only half of those with specific antibodies in serum 'outgrew' their disease so soon.